1989
DOI: 10.1002/lsm.1900090507
|View full text |Cite
|
Sign up to set email alerts
|

Transscleral cyclophotocoagulation using a contact laser probe: A histologic and clinical study in rabbits

Abstract: Transscleral photocoagulation of the ciliary body was achieved in pigmented rabbits using a sapphire probe delivery system coupled to a commercial surgical continuous-wave Nd:YAG laser. This contact technique was found to be effective in reducing intraocular pressure (IOP); greater treatment energies were associated with a more prolonged reduction in IOP, and also correlated with a greater degree of histologic damage to the ciliary body. Treatment energies of 0.8-1.0 Joules produced substantial disruption of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The contact treatment induces damage to the pigmented and nonpigmented epithelia and the stroma of ciliary processes, without a secondary effect to the overlying sclera [54]. The advantage of the contact procedure is to reduce the IOP using the same amount of energy than the that of the noncontact Nd:YAG procedure, but with an ability to deliver the energy sixty times lower, this leads to less tissue destruction and fewer postoperative complications.…”
Section: Cyclodestructive Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The contact treatment induces damage to the pigmented and nonpigmented epithelia and the stroma of ciliary processes, without a secondary effect to the overlying sclera [54]. The advantage of the contact procedure is to reduce the IOP using the same amount of energy than the that of the noncontact Nd:YAG procedure, but with an ability to deliver the energy sixty times lower, this leads to less tissue destruction and fewer postoperative complications.…”
Section: Cyclodestructive Techniquesmentioning
confidence: 99%
“…In addition, there are no long-term studies that evaluated the risk of hypotony after repeated insonifications or the risk of hypotony whether patients receive further filtration surgery. Despite no comparative randomized clinical trials have been performed, an overview of literature leads to a hypothesis that UC 3 might have a little lower efficacy (also in terms of reduction of number of medications) and provide a shorter duration of the IOP-lowering effect compared to that of the other cyclodestructive approaches, though with a greater safety profile [1619, 42, 43, 5469, 88]. On the other hand, the new probes seem to increase the IOP-lowering efficacy of the technique, maintaining the same level of safety.…”
Section: Miniaturized High-intensity Focused Ultrasounds For Cyclomentioning
confidence: 99%
“…28 Most clinical studies 15,19 have considered 4-6 weeks as the time frame for the response of DLCP, after which the eyes are re-treated. We waited for 6 weeks before re-treating our patients.…”
Section: Transcleral Diode Laser Cyclophotocoagulation S Kaushik Et Almentioning
confidence: 99%
“…Our results show that the light of Nd: YAG lasers (1,064 nm) and of diode lasers (804 nm) is well transmitted through the sclera and hardly absorbed in scleral tissue. This corresponds to the observation made in various histological studies that after Nd:YAG and diode laser cyclocoagulation at moderate energy levels, the tissue effects are confined to the ciliary body [2,8,10,12,[17][18][19]41,42]. Only at high-energy levels (5 J in a rabbit eye) far above the coagulation threshold and at long exposure times (300 ms to 2 s), was scleral damage found, obviously having been caused by heat conduction from the ciliary body into the sclera [8,411. Comparison of the laser effects in pigmented rabbits and albino rabbits has shown that cyclocoagulation relies on the light absorption in the ciliary pigment epithelium [1,43,441.…”
Section: Clinical Consequencesmentioning
confidence: 99%